Factors Affecting Fleet Charter Costs: Analysis of Market Uncertainty, Shipping Rates, Financial Capability, and Cost Structure - Atong Soekirman (Siber Nusantara of Economic and Finance Review, 2026)
This study aims to analyze the determinants of fleet charter costs through the variables of market uncertainty, shipping rates, financial capability, and cost structure. The study uses a qualitative approach with a systematic literature review (SLR) method on 30 national and internationally reputable scientific articles. Data are analyzed through the stages of reduction, presentation, and synthesis to produce a comprehensive conceptual model. This study contributes to the development of maritime transportation management literature with an integrative approach. Further research is recommended to test this model empirically using a quantitative approach and add other variables to improve the accuracy and generalization of the findings. The results of the study indicate that: 1) Market Uncertainty affects Fleet Charter Costs; 2) Shipping Rates affect Fleet Charter Costs; 3) Financial Capability affects Fleet Charter Costs; and 4) Cost Structure affects Fleet Charter Costs.